Ultimate Black Panther. Vol. 2, Gods and kings - Hill, Bryan Edward (Marvel Worldwide, Inc., 2025)
"The thrilling saga of the Black Panther in the Ultimate Universe continues! While T'Challa has sought to grow his power, so too have the forces of Moon Knight -- and with access to a unique new resource, Ra and Khonshu are stronger than ever! How will Wakanda stand in its resistance against the kings of the Upper and Lower Kingdoms? And is T'Challa prepared to bear the consequences of tapping into such dangerous wells of power? The time for planning is over -- now the Panther and Storm must mount a guerrilla counterstrike against Khonshu and Ra! Meanwhile, Killmonger and Okoye seek allies to aid their cause outside of Wakanda -- you won't believe the big gun they call in!